Sektorowy system innowacji jako instrument oceny innowacyjności przemysłu - Olczyk, Magdalena (The Sectoral System of Innovation as an Instrument of Industry Evaluation, 2009)
In this paper, the concept of the sectoral system of innovation (SSI) was discussed. SSI was defined as a set of new and established products for specific uses and a set of agents carrying out interactions for the creation, production and sale of those products. The author analyzed important elements of each SSI as: a knowledge base, actors and institutions. Moreover, the sixth typical model of the sectoral system of innovation was presented. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 760-768